2019
DOI: 10.1002/cncy.22151
|View full text |Cite
|
Sign up to set email alerts
|

Importance of anal cytology and screening for anal dysplasia in individuals living with HIV with an emphasis on women

Abstract: BACKGROUND:The incidence of squamous cell carcinoma of the anal canal has been increasing in high-risk populations.To the authors' knowledge, there is no international consensus regarding screening for squamous cell carcinoma of the anal canal, but screening is commonly comprised of a Papanicolaou (Pap) test in combination with digital anorectal examination followed by high-resolution anoscopy if necessary. The current study focused on individuals living with HIV and particularly on women living with HIV. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Our findings are similar to those observed among HIV‐positive women followed for 10 years. This research observed that ASC on anal cytology had a high risk of anal squamous intraepithelial lesion 22 . Although atypical anal cytology is low in the general population, it seems interesting to offer anal screening for risk groups.…”
Section: Discussionmentioning
confidence: 73%
“…Our findings are similar to those observed among HIV‐positive women followed for 10 years. This research observed that ASC on anal cytology had a high risk of anal squamous intraepithelial lesion 22 . Although atypical anal cytology is low in the general population, it seems interesting to offer anal screening for risk groups.…”
Section: Discussionmentioning
confidence: 73%
“…Collection of the anal specimens presents more difficulties than cervical samples, since it is performed blindly and with a larger mucosal surface. These issues can hinder obtaining a sample that represents the entire area subject to disease and can lead to lower diagnostic performance when compared to cervical cytology 16 . The same difficulties point to diagnostic limitations in HRA 17 besides the rugosity of the anal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Women with anal dysplasia almost always have a history of RAI and are likely to have concomitant cervical HPV localization and dysplasia. [ 39 40 ] High-grade cytology was found only in HIV-positive cases. Wu et al .…”
Section: Discussionmentioning
confidence: 99%